Interfering with interferon-γ signalling in intestinal epithelial cells: selective inhibition of apoptosis-maintained secretion of anti-inflammatory interleukin-18 binding protein - Schuhmann, Daniel Hermann; Godoy, Patricio; Weiß, Christel; Gerloff, Andreas; Singer, Manfred V.; Dooley, Steven; Böcker, Ulrich (Clinical & experimental immunology, 2011)
The intestinal epithelial barrier represents an important component in the pathogenesis of inflammatory bowel diseases. Interferon (IFN)-γ, a T helper type 1 (Th1) cytokine, regulated by the interleukin (IL)-18/IL-18 binding protein (bp) system, modulates the integrity of this barrier. The aim of this work was to study functionally the consequences of IFN-γ on intestinal epithelial cells (IEC) and to interfere selectively with identified adverse IFN-γ effects. IEC lines were stimulated with IFN-γ. IL-18 and IL-18bp were assessed by enzyme-linked immunosorbent assay. Staining of phosphatidylserine, DNA laddering, lactate dehydrogenase (LDH) release, cleavage of poly-adenosine diphosphate-ribose-polymerase (PARP) and activation of caspase-3 were analysed to determine cell death. Inhibitors of tyrosine kinase, caspase-3 or p38 mitogen-activated kinase ((MAP) activity were used. Cytokines were measured in supernatants of colonic biopsies of healthy controls and inflammatory bowel disease (IBD) patients. In IEC lines, IFN-γ up-regulated IL-18bp selectively. Ex vivo, IFN-γ was present in supernatants from cultured biopsies and up-regulated with inflammation. Contrary to previous reports, IFN-γ alone induced apoptosis in IEC lines, as demonstrated by phosphatidylserin staining, DNA cleavage and LDH release. Further, activation of caspase-3, PARP cleavage and expression of pro-apoptotic Bad were induced. Partial inhibition of caspase-3 and of p38 but not JAK tyrosine kinase, preserved up-regulation of IL-18bp expression. Selective inhibition of IFN-γ mediated apoptosis, while preserving its beneficial consequences on the ratio of IL-18/IL-18bp, could contribute to the integrity of the mucosal barrier in intestinal inflammation.
Published: 16 November 2010
Gesehen am 27.10.2022